Pengaruh Kualitas Produk Dan Merek Minuman Le Minerale Terhadap Minat Beli Konsumen Anak Muda Di Wilayah Kelurahan Penggilingan Jakarta Timur - Sylvia Theodara; Sri Ekowati P (Ikon --Jurnal Ilmiah Ilmu Komunikasi, 2021)
This time people are starting to like packaged beverage brands that tend to be more practical. This condition involves consumers being faced with various types of beverage brands, of course, with varying prices and good product quality that can convince people to buy these beverage products and in the end generate a sense of interest by consumers to buy. The company PT Tirta Fresindo Jaya in 2015 launched a beverage product branded Le Minerale. The purpose of this study was to determine the effect of Le Minerale Product Quality and Brand on Purchase Intention of Young Consumers in the Kelurahan Penggilingan, East Jakarta. The theory used in this research is marketing communication theory. As well as concepts related to communication research, product quality, brand, and purchase interest. This study uses a quantitative approach in an explanative form. To conduct this research the authors used two techniques, namely, data analysis techniques in the form of observation, questionnaires, and research data through literature studies. The total population is 28,240 and the sample used is 100. And this research method uses a survey method.The results showed that statistically it is clear that simultaneously the variables of Product Quality and Brand have a very strong influence on Consumer Purchase Interest in young people in the area of Penggilingan Village, East Jakarta. The conclusion of this research is that the quality of Le Minerale products and beverage brands is one proof that these drinks provide good quality so that Le Minerale can be liked and attracted by consumers.